Association of Skin Autofluorescence Levels With Kidney Function Decline in Patients With Peripheral Artery Disease. Issue 8 (August 2016) - Schutte, Elise; de Vos, Lisanne C.; Lutgers, Helen L.; Lambers Heerspink, Hiddo J.; Wolffenbuttel, Bruce H.R.; Vart, Priya; Zeebregts, Clark J.; Gansevoort, Ron T.; Lefrandt, Joop D.
Abstract : Objective—: Skin autofluorescence (SAF), a measure of advanced glycation end product accumulation, is associated with kidney function. We investigated the association of SAF with rate of kidney function decline in a cohort of patients with peripheral artery disease. Approach and Results—: We performed a post hoc analysis of an observational longitudinal cohort study. We included 471 patients with peripheral artery disease, and SAF was measured at baseline. Primary end point was rate of estimated glomerular filtration rate (eGFR) decline. Secondary end points were incidence of eGFR <60 and <45 mL/min/1.73 m 2 and rapid eGFR decline, defined as a decrease in eGFR of >5 mL/min/1.73 m 2 /y. During a median follow-up of 3 years, the mean change in eGFR per year was −1.8±4.4 mL/min/1.73 m 2 /y. No significant difference in rate of eGFR decline was observed per 1 arbitrary unit increase in SAF (−0.1 mL/min/1.73 m 2 /y; 95% confidence interval, −0.7 to 0.5; P =0.8). Analyses of the secondary end points showed that there was an association of SAF with incidence of eGFR <60 and <45 mL/min/1.73 m 2 (hazard ratio, 1.54; 95% confidence interval, 1.13–2.10; P =0.006 and hazard ratio, 1.76; 95% confidence interval, 1.20–2.59; P =0.004, respectively), but after adjustment for age and sex, significance was lost. There was no association of SAF with rapid eGFR decline. Conclusions—: In conclusion, in this cohort of patients with peripheral artery disease, elevated SAF was associated with lower baseline eGFR. Although SAF has previously been established as a predictor for cardiovascular disease and mortality, it did not predict the rate of kidney function decline during follow-up in this study. Abstract : Supplemental Digital Content is available in the text.